The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/app11020817
|View full text |Cite
|
Sign up to set email alerts
|

Review of Adaptive Shock Control Systems

Abstract: Drag reduction plays a major role in future aircraft design in order to lower emissions in aviation. In transonic flight, the transonic shock induces wave drag and thus increases the overall aircraft drag and hence emissions. In the past decades, shock control has been investigated intensively from an aerodynamic point of view and has proven its efficacy in terms of reducing wave drag. Furthermore, a number of concepts for shock control bumps (SCBs) that can adapt their position and height have been introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…In order to train shape memory alloys with suitable properties, Qiu et al [ 82 ] proposed a thermomechanical training program and designed a complete device for training two-way memory effects. Compared with traditional spoiler actuators or pressurized elements, shape memory alloy actuators have the advantages of small size and high controllability [ 83 ]. Balzarek et al [ 84 ] attempted to integrate SMA actuators into the helicopter’s wings to form an elastic skin for better hover flight capabilities.…”
Section: Shape Memory Materialsmentioning
confidence: 99%
“…In order to train shape memory alloys with suitable properties, Qiu et al [ 82 ] proposed a thermomechanical training program and designed a complete device for training two-way memory effects. Compared with traditional spoiler actuators or pressurized elements, shape memory alloy actuators have the advantages of small size and high controllability [ 83 ]. Balzarek et al [ 84 ] attempted to integrate SMA actuators into the helicopter’s wings to form an elastic skin for better hover flight capabilities.…”
Section: Shape Memory Materialsmentioning
confidence: 99%
“…A review of adaptive shock control systems and concepts can be found in [9]. A major challenge of morphing aircraft components is to implement a functionality that for example optimizes a shape in terms of aerodynamic behavior, and simultaneously to not increase the complexity of the overall system or its weight too much.…”
Section: Introductionmentioning
confidence: 99%
“…The common goal of the diverse range of concepts investigated to date is to adapt the aerodynamic shape of an aerofoil or wing to allow for optimal performance at multiple design points. Many technological concepts for adapting the camber, thickness, planform, twist, wing tips, adaptive bumps, etc., of fixed-wing aircraft may be found in comprehensive reviews of morphing aircraft research by Barbarino et al [1], Concilio et al [2], and Künnecke et al [3]. However, the applications for rotor blades are much more limited.…”
Section: Introductionmentioning
confidence: 99%